ANALYSIS OF SUPPLY CHAIN ​​RESILIENCE IN MSMES IN BANYUMAS DURING AND AFTER THE PANDEMIC COVID-19 - Gumintang, Bagas; Nikmah, Filda; Wijaya, Anas; Haryadi, Lintang; Delian, Almas; Putra, Farhan (This journal is published by the Vocational School of Universitas Sebelas Maret., 2000)
This research aims to analyze the learning process by MSMEs in Banyumas during the COVID-19 pandemic, which entered Indonesia in early March 2020, as well as develop strategies to support supply chain resilience. This research uses a case study design with a qualitative descriptive approach. Data collection was carried out through interviews and observations. The interview results were transcribed and analyzed using an analysis template through the coding obtained. The research results show that each MSME has its way of studying the business situation to maintain the supply chain during the COVID-19 pandemic. Some informants collaborated with online service applications because of government regulations regarding distance restrictions in public places, business environments, and facility changes. Limited external activities force business actors to make supply chain processes effective. Changes in the supply chain process impact supply adjustments, affecting the storage system according to the flow of raw materials in and out. The availability of raw materials and the level of customer demand influence production activities. MSME players are carrying out a learning process to survive during the COVID-19 pandemic by prioritizing profits. MSME players implement several strategies to maintain the supply chain during the learning process. These strategies can be developed based on the results of learning by MSME actors. Strategy development is carried out through credit restructuring, competing through promotions, collaboration between MSME players, product innovation based on learning experiences, improving support services, reducing company operational costs, and focusing on market targets.